Ink and bone - Caine, Rachel (2015)
"Ruthless and supremely powerful, the Great Library is now a presence in every major city, governing the flow of knowledge to the masses. Alchemy allows the Library to deliver the content of the greatest works of history instantly, but the personal ownership of books is expressly forbidden ... When his friend inadvertently commits heresy by creating a device that could change the world, Jess discovers that those who control the Great Library believe that knowledge is more valuable than any human life--and soon both heretics and books will burn"--Dust jacket flap.
Keywords: Alexandrian Library -- Juvenile fiction; Libraries -- Juvenile fiction; Books -- Juvenile fiction; Fantasy